2018
DOI: 10.1111/adj.12586
|View full text |Cite|
|
Sign up to set email alerts
|

Contemporary exodontia

Abstract: Exodontia is a cardinal skill of all dentists. Patients expect extractions to be skillfully and painlessly accomplished every time. It's not necessarily so simple and can be challenging. In this paper we explore contemporary issues of the full process of exodontia including diagnosis, technique, complication minimization as well as management of medically compromised patients with appropriate post-operative care, including pharmacotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
11
0
4
Order By: Relevance
“…Recent studies show that antibiotic prescription is not necessary in healthy patients as long as strict aseptic and antiseptic management is performed. [56][57][58] A lower percentage of dentists erroneously prescribed antibiotics during endodontic treatments without systemic symptoms (18.7 percent), periodontal treatment without surgery (11.7 percent), gingivitis (13.9 percent), anesthetic complications (4.9 percent), and pain (3.6 percent). Abbot 59 interviewed US dentists and endodontists to learn the prescription of antibiotics for different pulpal and periapical conditions and found that these professionals used Chi-square test to compare the awareness, attitudes, and intention to practice levels among dentists in the seven cities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that antibiotic prescription is not necessary in healthy patients as long as strict aseptic and antiseptic management is performed. [56][57][58] A lower percentage of dentists erroneously prescribed antibiotics during endodontic treatments without systemic symptoms (18.7 percent), periodontal treatment without surgery (11.7 percent), gingivitis (13.9 percent), anesthetic complications (4.9 percent), and pain (3.6 percent). Abbot 59 interviewed US dentists and endodontists to learn the prescription of antibiotics for different pulpal and periapical conditions and found that these professionals used Chi-square test to compare the awareness, attitudes, and intention to practice levels among dentists in the seven cities.…”
Section: Discussionmentioning
confidence: 99%
“…The indication is, therefore, also always a balancing of different requirements. In general, tooth extraction serves as a last resort when every other treatment option failed or is not indicated anymore [4].…”
Section: Introductionmentioning
confidence: 99%
“…En particular la exodoncia, uno de los procedimientos cardinales de la odontología, al ser una cirugía ambulatoria depende de un último factor que es ajeno a la pericia del tratante: el cuidado postoperatorio. (Sittitavornwong et al, 2005;Alvira-González & Gay-Escoda, 2015;Sambrook & Goss, 2018).…”
Section: Introductionunclassified
“…La exodoncia es un procedimiento ambulatorio frecuente, que puede presentar múltiples complicaciones (Pitekova et al, 2010;Solé Besoaín & Muñoz Thomson, 2012;Akinbami & Godspower, 2014;Hupp et al, 2014;Alvira-González & Gay-Escoda, 2015;Taberner-Vallverdú et al, 2017;Mamoun, 2018;Sambrook & Goss, 2018). Dentro de estos, se ha evaluado principalmente el consumo de tabaco, edad y género, uso de anticonceptivos, cantidad de anestesia utilizada, número de exodoncias en un acto quirúrgico, entre otros (Akinbami & Godspower, 2014;Taberner-Vallverdú et al, 2017;Mamoun, 2018).…”
Section: Introductionunclassified